Control of Imine Exchange Kinetics with Photoswitches to Modulate Self‐Healing in Polysiloxane Networks by Light Illumination. Issue 44 (8th July 2016) - Kathan, Michael; Kovaříček, Petr; Jurissek, Christoph; Senf, Antti; Dallmann, Andre; Thünemann, Andreas F.; Hecht, Stefan
Abstract: Various aldehyde‐containing photoswitches have been developed whose reactivity toward amines can be controlled externally. A thermally stable bifunctional diarylethene, which in its ring‐closed form exhibits imine formation accelerated by one order of magnitude, was used as a photoswitchable crosslinker and mixed with a commercially available amino‐functionalized polysiloxane to yield a rubbery material with viscoelastic and self‐healing properties that can be reversibly tuned by irradiation. Abstract : Illuminating dynamic covalent chemistry ! A photoswitch, which makes it possible to modulate the reactivity of aldehyde functionalities by light irradiation, was developed to control the exchange kinetics in a dynamic imine‐based polysiloxane network. In this way soft materials were obtained with remote control over their intrinsic properties, most notably their ability to self‐heal.